(untitled) (Research, Society and Development, 2022)
Objective: to analyze knowledge and practices about the bond between mother and newborn in the first hours of life with nursing professionals. Method: qualitative study, developed in a municipality of Mato Grosso, with nursing professionals who work directly in childbirth care and in the first hours of life. Data collection took place in January 2021 through an online questionnaire, analyzed by Minayo’s content analysis in the thematic analysis modality. Results: professionals are aware of the bond between mother and newborn, and practice bonding through skin-to-skin contact and breastfeeding in everyday life, however some interventionist procedures remain. Conclusion: the nursing team is qualified to carry out the promotion of the binomial bond through the care provided in the first hours of life. However, some interventionist care practiced by the team still persists. In this way, the periodic evaluation of the supervisors of the Amigo da Criança Hospital, combined with permanent education, contribute to the improvement of the assistance provided by this team.